2002
DOI: 10.1091/mbc.01-12-0569
|View full text |Cite
|
Sign up to set email alerts
|

Human Chromosomes 9, 12, and 15 Contain the Nucleation Sites of Stress-Induced Nuclear Bodies

Abstract: We previously reported the identification of a novel nuclear compartment detectable in heatshocked HeLa cells that we termed stress-induced Src-activated during mitosis nuclear body (SNB). This structure is the recruitment center for heat shock factor 1 and for a number of RNA processing factors, among a subset of Serine-Arginine splicing factors. In this article, we show that stress-induced SNBs are detectable in human but not in hamster cells. By means of hamsterϾhuman cell hybrids, we have identified three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
71
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 42 publications
2
71
0
Order By: Relevance
“…One hypothesis is that the presence of splicing factors merely reflects the splicing of sat III transcripts, as strongly supported by our findings that sat III and hsp90α transcripts, but not the intronless hsp70 transcripts, are complexed with snRNPs in vivo. In this case, the particular composition of the splicing complexes present in the granules, containing some but not all splicing factors (Chiodi et al, 2000;Denegri et al, 2001;Denegri et al, 2002;Weighardt et al, 1999), might specify a certain type of transcript. Another possibility is that the binding of splicing factors to these transcripts plays a role in their stabilization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One hypothesis is that the presence of splicing factors merely reflects the splicing of sat III transcripts, as strongly supported by our findings that sat III and hsp90α transcripts, but not the intronless hsp70 transcripts, are complexed with snRNPs in vivo. In this case, the particular composition of the splicing complexes present in the granules, containing some but not all splicing factors (Chiodi et al, 2000;Denegri et al, 2001;Denegri et al, 2002;Weighardt et al, 1999), might specify a certain type of transcript. Another possibility is that the binding of splicing factors to these transcripts plays a role in their stabilization.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, certain splicing factors such as the hnRNP HAP and the serine/arginine-rich (SR) proteins 9G8, SF2/ASF and SRp30c have been shown to relocalize upon stress to nuclear stress granules, whereas others, such as small nuclear ribonucleoproteins (snRNPs) or SC35, do not, suggesting a possible mechanism to regulate splicing activity during stress by the sequestration of certain splicing factors within particular subnuclear regions (Chiodi et al, 2000;Denegri et al, 2001;Denegri et al, 2002;Weighardt et al, 1999).…”
mentioning
confidence: 99%
“…Furthermore, Mathew et al (Mathew et al, 2001) have reported that, in murine fibroblasts, HSF2 has the biochemical properties of a temperature-sensitive protein because, upon heat shock, HSF2 is localized to the perinuclear region, its solubility is decreased and DNA-binding activity is diminished. This intriguing difference between human and murine cells has also been observed with HSF1, because the stress-induced subnuclear compartmentalization of HSF1 has been detected only in human cells (Sarge et al, 1993;Denegri et al, 2002). Altogether, direct evidence of HSF2, human or murine, being a physiological transcriptional regulator of heat shock genes is missing.…”
mentioning
confidence: 97%
“…Recently, stress granules were revealed to associate with human chromosome 9q11-q12, corresponding to a large block of heterochromatin composed primarily of satellite III repeats adjacent to the centromere (Jolly et al, 2002). Furthermore, Denegri et al (Denegri et al, 2002) have reported that, in addition to chromosome 9, chromosomes 12 and 15 also contain nucleation sites for stress granules. The functional significance of stress granules is still unknown.…”
mentioning
confidence: 99%
“…Within this locus, HSF1 binds through direct DNA-protein interaction with a nucleosome-containing subclass of satellite III repeats [20]. In addition to chromosome 9, chromosomes 12 and 15 also contain the nucleation sites of stress bodies in heat-shocked HeLa cells [21].…”
Section: Introductionmentioning
confidence: 99%